Remote Learning, Distance Education and Online Learning During the COVID19 Pandemic : A Resource List by the World Bank's Edtech Team - World Bank (World Bank, Washington, DC, 2020)
The selection of resources and platforms that you will find here has been elaborated in order to facilitate the rapid identification of helpful technological solutions that could be used to support remote learning. The resource list is regularly curated and organized by the World Bank's Edtech team.